The Spin‐Forbidden Reaction of Ground‐State Sulfur Atoms with Ethylene. Issue 3 (25th January 2016) - Thompson, Kristopher M.; Gao, Yide; Marshall, Paul
ABSTRACT: Ground‐state S‐atoms ( 3 PJ ) were generated by pulsed laser photolysis of carbonyl sulfide (OCS) precursor and monitored by time‐resolved resonance fluorescence. The kinetics were studied over the temperature range of 291–1052 K. Below 900 K, the effective bimolecular rate constant k 1 was found to be independent of pressure and also to be in good accord with prior measurements made at 442 K and below. At higher temperatures, fall‐off curves were characterized. These demonstrate that the reaction is dominated by addition. The high‐pressure limit is summarized as k∞ = 1.5 × 10 −11 exp(−8.4 kJ mol −1 / RT ) cm 3 molecule −1 s −1 . The low‐pressure limiting rate constant is also obtained. The observation of formation of one or more adducts even at ∼1000 K constrains their thermochemistry, and comparison with the computed reaction enthalpies for various candidates in the literature shows the addition products can only be accessed via intersystem crossing. Estimated Rice–Ramsperger–Kassel–Marcus (RRKM) addition rate constants at the low‐pressure limit for formation of vinylthiol and ethanethial are in accord with the observed kinetics assuming that the collisional efficiency near 1000 K is about 0.1.